White-nosed Coati (Nasua narica) a predator of the Yellow-headed Caecilian (Oscaecilia ochrocephala) in Panama: Coatí de nariz blanca (Nasua narica), un depredador de la cecilia de cabeza amarilla (Oscaecilia ochrocephala) en Panamá - Fuentes, Rogemif (Revista Científica Vida Natural, 2024)
We report a rare event of predation by the White-nosed Coati (Nasua narica) on the Yellow-headed Cecilia (Oscaecilia ochrocephala), during the wildlife monitoring, rescue and relocation process of the “Cerro Cucaracha” project within the Canal de Panama, through direct observation and photographic recording, this predator-prey relationship has been scarcely documented in Panama, with which we make a valuable contribution to the knowledge of this ecological interaction; considering that to expand this type of records it is necessary to increase the observation time in the field or implement sampling methodologies such as camera trap stations.